Rancang Bangun E-Commerce Kopma Sale UNHAS Berbasis Web Untuk Kegiatan Kewirausahaan - Andi Muh. Ibnu Hibban Bagoes Malolo; Muhammad Fikri; Dhiyaa Unnisa; Riskawati Riskawati; Eliyah A M Sampetoding; A. Muh. Amil Siddik; Esther S Manapa (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
UnhasCooperative UKM is a student activity unit engaged in the field of entrepreneurship. The entrepreneurial activity of Unhas Cooperative UKM students provides opportunities for students who have an interest in entrepreneurship to create business activities through analysis of market needs and opportunities. However, the entrepreneurship activities of the Unhas Cooperative UKM are still considered to be ineffective in their marketing system because the method used is still applying the conventional system, namely only through social media so that it has not been able to maximize its entrepreneurial potential. Departing from these problems, a web-based e-commerce was created entitled "Kopma Sale: Designing web-based e-commerce to support entrepreneurial activities" Unhas cooperative ukm. The development of web-based e-commerce has advantages in terms of marketing because of a wider network reach and can describe the products being sold in detail and is able to actively interact with the market. This website is expected to be able to support and increase the entrepreneurial activities of Unhas cooperative SMEs. The method used in this research is a literature-based qualitative method, by involving participants to dig up information relevant to research with the aim of producing website pages that can be developed according to the needs of Unhas cooperative SMEs. This website is designed using the waterfall model SDLC. The results of the research are in the form of a "kopma sale" website which is expected to be utilized in the entrepreneurship activities of Unhas cooperative SMEs.